2005
DOI: 10.1002/ana.20638
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion computed tomography: Prediction of final infarct extent and stroke outcome

Abstract: The Alberta Stroke Program Early Computed Tomography Score (ASPECTS) has not been previously applied to perfusion CT (CTP). Five raters assigned ASPECTS to baseline noncontrast CT (NCCT), CT angiography source images (CTA-SI), CTP source images (CTP-SI), and CTP maps of cerebral blood volume (CBV), cerebral blood flow (CBF), and mean transit time (MTT) from 37 consecutive patients with less than 6-hour anterior circulation ischemic stroke. Major reperfusion was identified on follow-up imaging. Mean baseline AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
182
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 196 publications
(196 citation statements)
references
References 17 publications
14
182
0
Order By: Relevance
“…7 Compared to CTASI, perfusion CT (CTP) better delineates the ischemic core and can identify areas of salvageable brain tissue in anterior circulation stroke. 24,25 Similar findings in the posterior circulation are conceivable. Comparison of CTA, CTP and multimodal MRI to predict outcome and treatment response in patients with BAO could be subject of future studies.…”
Section: Discussionsupporting
confidence: 55%
“…7 Compared to CTASI, perfusion CT (CTP) better delineates the ischemic core and can identify areas of salvageable brain tissue in anterior circulation stroke. 24,25 Similar findings in the posterior circulation are conceivable. Comparison of CTA, CTP and multimodal MRI to predict outcome and treatment response in patients with BAO could be subject of future studies.…”
Section: Discussionsupporting
confidence: 55%
“…Parsons et al 10 reported similar findings in a prospective subcohort of 20 patients with MCA stroke, imaged within 6 hours of symptom onset, who achieved major reperfusion. We were particularly interested in the comparison of ASPECTS between CT perfusion CBV maps and CTA source images because both techniques have been shown to provide benefit over noncontrast CT. [7][8][9][10][11] We believe that CT perfusion CBV maps outperformed CTA source images in this study because of the inherent technical difference in determining blood volume between the 2 techniques. CTA source images provide an estimate of CBV by revealing regions of decreased enhancement but do so in a single "snapshot" during peak contrast enhancement.…”
Section: Discussionmentioning
confidence: 60%
“…We cautiously used the traditional cut-point of Յ7 in a brief subanalysis of our main results, but this may not be optimal for CT perfusion CBV maps. Parsons et al 10 and, more recently, Kloska et al 12 demonstrated better predictability of 90-day mRS with a cut-point of Յ6, whereas Aviv et al 11 recently reported an optimal cut-point of Յ8. The latter study had a lack of direct recanalization data and a small sam-ple size (only 7 patients had evidence of reperfusion).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations